2012
DOI: 10.15407/spqeo15.04.340
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence studies of CdTe polycrystalline films

Abstract: Photoluminescence (PL) studies of CdTe polycrystalline films are reported. The films were grown using the modified close space sublimation technique on sapphire substrates. The mean grain size in the investigated films was ranged from 10 up to 360 μm. The distinct spectral bands around 1.580 and 1.440 eV were observed at 77 K. These bands are attributed to shallow bound excitons at dislocations and deep defects, respectively. The intensity of luminescence related to dislocation defects is found to be proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the above estimation, the spatial distribution of defects is assumed to be uniform. However, it has been previously shown that in the investigated films the grain boundaries are represented by the dislocation network [23]. Taking into account the gettering effect of dislocations in polycrystalline films [24], this result implies inhomogeneous distribution of impurities in the intragrain regions.…”
Section: Resultsmentioning
confidence: 94%
“…In the above estimation, the spatial distribution of defects is assumed to be uniform. However, it has been previously shown that in the investigated films the grain boundaries are represented by the dislocation network [23]. Taking into account the gettering effect of dislocations in polycrystalline films [24], this result implies inhomogeneous distribution of impurities in the intragrain regions.…”
Section: Resultsmentioning
confidence: 94%
“…7,8 The direct gap of this material allows the generation of a significant cathodoluminescence signal CL, which facilitates its theoretical study in terms of some important parameters influencing several industrial applications. The different results are obtained using the generation function of Wu and Wittry 9 adjusted to CdTe.…”
Section: Introductionmentioning
confidence: 99%